Discourses on Religious Diversity Explorations in an Urban Ecology. - Stringer, Martin D. (Farnham : Ashgate Publishing Ltd, 2013)
Stringer explores the series of discourses around religion and religious diversity that are held by ordinary members of the city. Drawing on examples from UK, Europe and the US, Stringer offers some practical suggestions for ways in which discourses of religious diversity can be managed in the future. Students in the fields of religious studies, sociology, anthropology and urban studies; practitioners involved in inter-religious discussions; church and faith leaders; and politicians should all find this book an invaluable addition to on-going debates.
Cover; Contents; List of Tables; Acknowledgements; 1 Religion and Urban Theory; 2 Discourses of Diversity; 3 The Two Towers; 4 Religion in a Context of Super-diversity; 5 Taking to the Streets; 6 The Year of the Golden Pig; 7 Urban Memory; 8 Managing Discourses of Religious Diversity; Bibliography; Index.
Print version record.
Includes bibliographical references and index.
Keywords: Cities and towns -- Religious aspects; Cultural pluralism -- Religious aspects; Religious pluralism; Cultural pluralism -- Great Britain -- Public opinion; Cultural pluralism -- Europe -- Public opinion; Cultural pluralism -- United States -- Public opinion; City dwellers -- Religious life -- Case studies; City dwellers -- Attitudes -- Case studies; Public opinion -- Great Britain; Public opinion -- Europe; Public opinion -- United States; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; Electronic books; Electronic books